Activation of the WNT-BMP-FGF Regulatory Network Induces the Onset of Cell Death in Anterior Mesodermal Cells to Establish the ANZ - Díaz-Hernández, Martha Elena; Galván-Hernández, Claudio Iván; Marín-Llera, Jessica Cristina; Camargo-Sosa, Karen; Bustamante, Marcia; Wischin, Sabina; Chimal-Monroy, Jesús (Frontiers in Cell and Developmental Biology, 2021)
The spatiotemporal control of programmed cell death (PCD) plays a significant role in sculpting the limb. In the early avian limb bud, the anterior necrotic zone (ANZ) and the posterior necrotic zone (PNZ) are two cell death regions associated with digit number reduction. In this study, we evaluated the first events triggered by the FGF, BMP, and WNT signaling interactions to initiate cell death in the anterior margin of the limb to establish the ANZ. This study demonstrates that in a period of two to eight hours after the inhibition of WNT or FGF signaling or the activation of BMP signaling, cell death was induced in the anterior margin of the limb concomitantly with the regulation of Dkk, Fgf8, and Bmp4 expression. Comparing the gene expression profile between the ANZ and the undifferentiated zone at 22HH and 25HH and between the ANZ of 22HH and 25HH stages correlates with functional programs controlled by the regulatory network FGF, BMP, and WNT signaling in the anterior margin of the limb. This work provides novel insights to recognize a negative feedback loop between FGF8, BMP4, and DKK to control the onset of cell death in the anterior margin of the limb to the establishment of the ANZ.